Mental Health Status and Coping Strategies of Chinese University Students During the COVID-19 Pandemic: A Rapid Review - Luo, W; Mohammed, J (Public Library of Science (PLoS), 2023)
Since the coronavirus (COVID-19) outbreak in December 2019, students have been under unparalleled psychological stress worldwide. As part of its prevention and control strategies, the Chinese Ministry of Education proposed online teaching activities for universities. For the first time, teaching and learning shifted completely online, significantly impacting university students used to classroom learning. This research addresses the knowledge gap about the mental health and coping strategies employed by Chinese university students during the COVID-19 pandemic. Electronic databases (PsycINFO, Scopus, Medline, Cochranes and CNKI) were searched systematically from 2019 to 2023, as part of this literature review. From the 349 articles found, 25 met the inclusion criteria for analysis. Thematic analysis was used to identify six sub-themes, organized under two main themes: Mental health issues of Chinese university students and their coping mechanisms. Heightened stress, anxiety, and depression appeared in Chinese university students during the pandemic, which may have been compounded by their isolation and the disruptions to their studies. Although the impact of COVID-19 on Chinese university students is waning, this study emphasizes the potential long-lasting impact on their mental health, which requires further investigation, particularly regarding gender differences. Moreover, positive and negative coping strategies were found in this review. Strategies for seeking social and family support and participating in sports activities had significant alleviating effects, while negative coping strategies such as alcohol-use and smoking did not. This rapid review informs the development of policies and interventions to enhance the mental health of university students during crisis events. The findings serve to inform health policymakers, university psychologists, and educators in improving the well-being of this student population.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; 39 Education; Behavioral and Social Science; Mental Health; Mental health; 3 Good Health and Well Being; General Science & Technology; Humans; COVID-19; Pandemics; Coping Skills; Universities; SARS-CoV-2; Students; Health Status; Humans; Health Status; Students; Universities; Pandemics; COVID-19; SARS-CoV-2; Coping Skills; Humans; COVID-19; Pandemics; Coping Skills; Universities; SARS-CoV-2; Students; Health Status